Studies on the hygienic quality of ice-erearn consumed in elazığ and the correlation between the general colony counts and methylene blue reduction time - Cemal Çelik; Bahri Patır; Süreyya Saltan; Abamüslüm Güven (Eurasian Journal of Veterinary Sciences)
The purpose of this study was to determine the hygienic quality of ıce-cream in Elazığ. 60 ıce-cream samples were examined. The average number of total viable aerob colony was found to be 1.6 x 107/g., Coliforms was 4.3 x 104/g., Staphylococcus was 8.7 x 104/g., Coagulase-positive Staphylococcus was 4.1 x 104/g., Faecal Streptococcus was 2.8 X 104/g ., yeasts and molds was 8.5 x 104/g. The correlation between the general viable colony count and the methylene blue reduction time was found to be significant ( p < 0.01 ). In conclusion, the hygienic qualities of the ıce-cream samples examined were low and didn't fit to the recommended microbiological standards.